GE_GERICHTE C/15431/2011 vom 17. Januar 2014 - GE Cour de justice (2014)
BAIL À LOYER; NATURE JURIDIQUE; RÉSILIATION; PRINCIPE DE LA BONNE FOI; PROLONGATION DU BAIL À LOYER | CO.261.2.A; CO.271; Cst.29.2